MITOS DAN HIPERREALITAS KOMUNIKASI POLITIK (Studi Iklan Pemilu Jusuf Kalla-Wiranto Versi Humble dan Mampu) - Masduki, Anang (Universitas Negeri Yogyakarta, 2015)
One of the main elements in a modern democratic politics is widespread political advertisement. In the 2009 election in Indonesia, one of the main partner, namely Jusuf Kalla and Wiranto also do advertising, especially on television. This is done to boost the popularity and elektabilitasnya to win the election. And in these ads are myths and hyperreality. This study was conducted to uncover the myths and hyperreality that exist in the ad with the title